Maximal power production as a function of sex and training status - Miller, R. M.; Freitas, E. D.; Heishman, A. D.; Kaur, J.; Koziol, K. J.; Galletti, B. A.; Bemben, M. G. (Biology of Sport, 2019)
Maximal muscular power is achieved at lower percentages of maximal strength (1RM); however, this notion has not been elucidated based on sex or training status. Therefore, the purpose of this investigation was to examine the influence of sex and training status on maximal power production. Sixty men and women (resistance trained or untrained) completed 1RM testing for the two-leg press (2LP) and bench press (BP). Participants then returned to perform single repetitions at 20, 30, 40, 50, 60, 70 and 80% of their 1RM to determine muscular power. Factorial analyses determined significant interactions (training status by sex by intensity) for the BP (F=35.6, p<0.001) and 2LP (F=8.2, p<0.001). Subsequent analyses indicated that during the BP trained men produce maximal power between 30-40% 1RM compared to untrained men at 60-70% 1RM. Trained women produced maximal power at 50% 1RM compared to untrained women at 60-70% 1RM. During the 2LP, trained men produced maximal power at 40% 1RM compared to untrained men at 60% 1RM. Trained women produced maximal power at 50% 1RM compared to 60-70% 1RM in untrained women. These data suggest that resistance trained individuals and men display maximal power at a lower relative intensity than untrained individuals and women.